A STRUCTURAL-FUNCTIONAL MODEL OF THE PEDAGOGICAL SYSTEM OF FORMING OF AESTHETIC CULTURE OF FUTURE TEACHERS OF THE UKRAINIAN LANGUAGE AND LITERATURE: COMPARATIVE EXPERIENCE - Papushina, Valentyna (Educological discourse, 2019)
The article is dictated by the need for changes in the educational process of higher educational establishment, the search for new forms, methods and means of forming the aesthetic culture of future teachers of Ukrainian language and literature. The author proposes the model development of the pedagogical system, tested in educational process of higher educational establishments. The author considers models of the pedagogical system which was tested in the educational process. The model is based on a systematic approach that structures the external and internal contexts of the formation of aesthetic culture of future teachers of Ukrainian language and literature and functional blocks: a target one that contains the purpose and objectives of the pedagogical system; theoretical and methodological, which includes the principles and approaches that base the process of forming the aesthetic culture of future teachers of Ukrainian language and literature; content and activity that covers the stages, components of the formation of aesthetic culture of future teachers of Ukrainian language and literature, technology of implementation of the pedagogical system, which require appropriate norms, methods, tools; a result, which defines the criteria for the formation of aesthetic culture of future teachers of Ukrainian language and literature, which, in turn, detail the indicators, and the levels of its formation.